Investment Banks in Egypt and Ghana: A Case Study of EFG Hermes in Ghana Versus HC Securities & Investment in Egypt. - Dr. Karim Badr El-Din Attia Hassanien, (IJRDO - Journal of Business Management, 2019)
Investment banks serve as intermediate between providers and users of funds. The purpose of this study is to compare between small investments banks in Egypt and Ghana as part of the financial sectors to provide financial tools and advices for investors in the financial markets. This promotes economic growth by improving the efficiency of the financial sectors. This study compares the factors that affect small investment banks in Egypt and Ghana such as the types of investment banking, population, capital markets, competition, economic conditions, and political conditions.Ghana is small in size in terms of investment banking as it has faced several problems over the last decades, while Egypt performed better over the same period. The objective of this study is to explore the difference in behavior, transactions between firms and companies, and to investigate the long run growth effects. Accordingly, the following is a comparison between different types of investment banks:Equity capital rising (through initial public offerings “IPOs”, follow on offerings, and equity – linked “convertible”).Mergers and acquisitions- M&A (through buy side, sell side, split offs, hostile defense, hostile takeovers, proxy fights, and joint ventures).Debt-capital-raising (high – grade or investment grade, high – yield, syndicated loans, and tax – exempted funds).Financial sponsors, leveraged finance, restructuring, ratings, securitized products, consumer retail and healthcare, technology , media, telecoms, natural resources and corporate finance.These operations are done to match with the other tasks of investment banks including mainly client relationship management, idea generation and problem solving, financial analysis, communication, assessment of opportunities, negotiation and structuring transactions, identify of potential investors, due diligence, and documentation.